2002
DOI: 10.1029/2001jd000779
|View full text |Cite
|
Sign up to set email alerts
|

A thermal dissociation laser‐induced fluorescence instrument for in situ detection of NO2, peroxy nitrates, alkyl nitrates, and HNO3

Abstract: [1] This paper describes a new instrument that uses a combination of thermal dissociation and laserinduced fluorescence detection of NO 2 for in situ detection of the sum total peroxy nitrates, the sum total of alkyl nitrates and hydroxyalkyl nitrates, and HNO 3 . The instrument is capable of routine, continuous in situ measurements of these three classes of compounds that are accurate (15%) with a low detection limit (90 parts per trillion (ppt) 10 s À1 , S/N ratio = 2 on a background of 1 ppb NO 2 and 30 ppt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
403
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 298 publications
(423 citation statements)
references
References 46 publications
16
403
3
Order By: Relevance
“…41 Gas phase nitric acid (HNO 3 ) was measured by CIMS in 2007 and laser induced fluorescence (LIF) in 2009. 42,43 NO 2 was measured at several heights during both campaigns using LIF 44,45 and in this work measurements from the 9.3 m height were used. In 2009, NO was also measured using a custom-built chemiluminescence instrument.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…41 Gas phase nitric acid (HNO 3 ) was measured by CIMS in 2007 and laser induced fluorescence (LIF) in 2009. 42,43 NO 2 was measured at several heights during both campaigns using LIF 44,45 and in this work measurements from the 9.3 m height were used. In 2009, NO was also measured using a custom-built chemiluminescence instrument.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The aerosol flow is then heated so that particles are vaporized to their gas phase precursors and detected using TD-LIF by which RONO 2 is thermally converted to RO + NO 2 and NO 2 is detected by LIF (10). A schematic of the instrument inlet system used in this study is shown in Figure 1.…”
Section: Instrument Design and Evaluationmentioning
confidence: 99%
“…Alkyl nitrates and nitric acid (HNO 3 ) are quantified by sampling through a heated inlet which thermally dissociates these molecules to NO 2 and a corresponding radical. The method has been compared to independent approaches for detection of NO 2 (28,29), total peroxy nitrates (ΣPN) (27) and ΣAN TD-LIF has previously been used to quantify various classes of gas + particle NO y by taking the difference in LIF signals measured with two inlets at two different temperatures (10). For the application described in this work, gas phase species including NO 2 are separated from particles before entering the heated portion of the inlet, and thus no subtraction is required.…”
Section: Thermal Dissociation Laser Induced Fluorescencementioning
confidence: 99%
“…NO 2 , PNs, and ANs were measured using the Berkeley thermal dissociation-laser induced fluorescence instrument (Thornton et al, 2000;Day et al, 2002). Briefly, gas is pulled simultaneously through four channels consisting of heated quartz tubes maintained at specific temperatures for the dissociation of each compound class above.…”
Section: Measurementsmentioning
confidence: 99%
“…Here we present observations of ANs, measured by thermal dissociation coupled to laser-induced fluorescence detection of NO 2 (Thornton et al, 2000;Day et al, 2002), in and downwind of Mexico City using the NASA DC-8 platform during the Megacity Initiative: Local and Global Research Observations (MILAGRO) phase of the INTEX-B campaign in the spring of 2006 (Singh et al, 2009;Molina et al, 2010). The aircraft flights targeted plume evolution and crossed the Mexico City plume at its origin and at distances as far as 1000 km downwind.…”
mentioning
confidence: 99%